Anthroposcenic Performance and the Need For 'Deep Dramaturgy'. (17th November 2019) - Stevens, Lara
Abstract : In this article I ask: what do we need to relinquish from current ways of doing theatre and what do we need to restore so that performance can play a productive role in responding to the climate emergency? What does it mean to make theatre in the age of the Anthropocene and in the face of potential social collapse or even human extinction? In attempting to think through Anthroposcenic performance or 'deep dramaturgy', I will consider a series of performances devised by Colombian-born, Sydney-based artist Maria Fernanda Cardoso, the Cardoso Flea Circus 1994(-2000) and The Art of Seduction (2016/2018).